Effect of crystalloid solution co-loading infusion rate on the dose requirements of prophylactic phenylephrine for preventing hypotension following combined spinal-epidural anesthesia for cesarean delivery - Xiao-Min Zhang; Jing Qian; Lin Liu; Yue-Ping Shen; Fei Xiao (BMC, 2024)
Abstract Background Intravenous fluid administration and prophylactic vasopressor infusion are the primary methods for preventing spinal anesthesia-induced hypotension during cesarean delivery. However, evidence regarding the impact of different volumes of crystalloid solution on the phenylephrine infusion dosage for preventing this hypotension remains inconclusive. This study aimed to determine the effect of two IV fluid infusion rates (10 or 20 mL/kg/h) on phenylephrine requirement for preventing spinal anesthesia-induced hypotension. Methods Eighty healthy parturients undergoing elective cesarean delivery under combined spinal-epidural anesthesia were enrolled. Participants were randomly assigned to receive either 10 mL/kg/h (group 10) or 20 mL/kg/h (group 20) of lactated Ringer's solution. The first patient in each group received 0.5 µg/kg/min of phenylephrine infusion immediately after intrathecal injection. The phenylephrine dose in subsequent patients was adjusted by increments or decrements of 0.05 µg/kg/min based on the previous patient's response. The ED50 of phenylephrine infusion for preventing spinal-induced hypotension for cesarean delivery was estimated using a modified up-down sequential analysis, with probit analysis applied as a backup sensitivity analysis. Results The ED50 values for preventing spinal anesthesia-induced hypotension were 0.30 µg/kg/min (95% CI, 0.29-0.32 µg/kg/min) for group 10, and 0.19 µg/kg/min (95% CI, 0.16-0.22 µg/kg/min) for group 20, respectively. The estimated relative potency for phenylephrine in group 10 compared to group 20 was 1.52 (95%CI, 1.24-1.97), showing a significant difference in the ED50 values between the two groups. Conclusion This study found that a higher crystalloid co-loading rate significantly reduces prophylactic phenylephrine requirement for preventing spinal anesthesia induced hypotension. Trials registration https://www.chictr.org.cn/showproj.html?proj=125918 (Trial number: ChiCTR2100048002).